Foliar application of potassium nitrate affects the growth and photosynthesis in coriander (Coriander sativum L.) plants under salinity - Elhindi, Khalid Mohammed; El-Hendawy, Salah; Abdel-Salam, Eslam; Schmidhalter, Urs; Rahman, Shafiq ur; Hassan, Al-Adl (Progress in Nutrition, 2016)
This investigation was carried out to study the effect of foliar application of K as potassium nitrate (KNO3) ability to mitigate the negative impacts of salinity on coriander (Coriander sativum L.) plants. In a greenhouse condition we used three levels of NaCl (0, 40 and 80 mM) applied to the growth medium and three levels of K as KNO3 (0, 50 and 100 mM) adjusted two times as a foliar spray on the plants. Salt stress affected adversely the growth rate, relative content of leaf water, the plant contents of protein and chlorophyll, attributes of gas exchange containing net CO2 assimilation rate, transpiration rate, stomatal conductance and substomatal CO2 concentration, essential oil content and leaf K+, Mg2+, P, Ca2+, N as well as Na+/K+ ratio, while it enhanced the electrolyte leakage, the plant contents of proline and Na+. It can be concluded that the tested parameters were generally positively affected by the foliar application of the KNO3 under saline and control conditions. Supplied with KNO3 treatment significantly showed better tolerance towards salinity. This can be explained by the positive effects of all external KNO3 application on the membrane permeability, photosynthetic activities, relative water content and nutrients balance and concentration under salinity stress conditions.